(3GdTaG HJYQja Mbhb GdeUWais - (3GdjMUHj, CHh GdaVd, GdbGVj YjGV, YjGV Hf ehSi Hf YjGV, J(B544(3g`s
(3ChdgG (B:s
(3bGd GdbGVj YjGV Hf ehSi Hf YjGV GdMeO ddg GdefaQO HGSeg GdCSei GdeNJU HGdedc GdCYR GdCSei GdPj djS Ohfg efJgi hdG hQGAg eQei GdXGgQ dG JNjdG hhgeG hGdHGWf JbOSG dG YOeG hSY cd TjA QMeI hYdeGs
(3BNQgG (B:s
(3fGbU GdBNQ hjfJgj YfO bhdg(B: (3aEPG CfG HGHf GdNdGdI YjSi GHf eQje hjMji Hf RcQjG YdjgeG GdUdGI hGdSdGe aQMHG Hj hOYG dj HNjQ Ke YQL HfG Edi GdSeGAs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 5 / 99s
(3eYLe GdeDdajf(B: 2 / 588s
(3cTa GdXfhf(B: 2 / 1052s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdJGQjNs